Volatile constituents from the infected wood of aquilaria malaccensis Benth - Karim B. Yaacob; Daniel Joulain (Universiti Kebangsaan Malaysia, 2000)
Upon hydrodistillation of Malaysian ‘gaharu’ (agarwood), an essential oil is obtained in 0.8% yield. The odour of the oil can be described as warm, diffusive, strongly woody and characteristic. It was found to contain at least 61% sesquiterpene alcohols, with 10-epi γ - eudesmol (23%) and valerianol (12.3%) predominating. The remaining part of the oils is made of sesquiterpene oxides (α - agarofurane : 7.5% major) and a number of non terpenic aromatic compounds (benzylacetone: major). These findings and other considerations conform the identity of the starting material is Aquilaria malaccensis Benth.